A study of the factors associated with cyberloafing behaviours in the Chinese education industry - Han, Bo (2022)
This dissertation is aimed at investigating the factors associated with cyberloafing behaviours in the Chinese education industry and provides proposed recommendations and measures for human resource management practices to help companies control and manage cyberloafing. This dissertation has applied the quantitative research method to conduct an online questionnaire survey of 284 Chinese teachers to examine whether social norms, job characteristics, job involvement and Internet skills are associated with cyberloafing behaviours of employees in the education industry in China. The data was then analysed on SPSS through appropriate statistical methods, and the results were compared with previous research and theory. Ultimately, this dissertation concludes the significant correlation between four factors and cyberloafing in the Chinese education industry, filling the gap in this field.